Hydrotherapy as a treatment for non-specific low back pain: a systematic review - Bhat, Ishfaq Bashir; Mohd Najib, Amirah Syahirah (IIUM Press, International Islamic University Malaysia, 2023)
Introduction: Properties of water like viscosity, buoyancy, and thermodynamics in hydrotherapy have been utilized to manage numerous musculoskeletal conditions, including non-specific low back pain (NSLBP). People with NSLBP experienced increased disability and depression. Vast of reviews regarding general management of low back pain in physical therapy was done. However, the review of the specific population of NSLBP and hydrotherapy is limited. Therefore, this study aims to systematically review randomized controlled trials on the effectiveness of hydrotherapy as management for NSLBP. Methods: The data were searched using synonyms for "Hydrotherapy" and "NSLBP" within 2009 to 2019. The databases from the allied health science’s field like Cinahl, Wiley Online Library, Taylor and Francis Online, Scopus, Science Direct, and Oxford Academic. The study selection was guided by inclusion criteria that had been justified. Results From 214 articles, only eight articles were included. The articles were appraised and extracted by using the McMaster Critical Review Form for Quantitative Studies. The two poor methodological quality studies were excluded from the critical review due to insufficient information to assist the study. The methodological quality of the six included articles ranged from ''fair'' to ''very good''. Conclusion There was a significant reduction in pre and post visual analog score (VAS) in the hydrotherapy group compared to no hydrotherapy group. However, the no hydrotherapy group reported a reduction of VAS but not significant. In conclusion, hydrotherapy offers a greater reduction of pain compared to no hydrotherapy group. Future research should include higher methodological quality studies to support the current finding.